Anteseden Keberhasilan Eksekusi Strategi: Sebuah Model dan Proposisi Berdasarkan Studi Kasus di Industri Telekomunikasi - Tarigan, Samuel (Yayasan Petra Harapan Bangsa, 2010)
Executing strategy is often more difficult than formulating it, and executional capability will eventually separate a firm’s performance than its competitors’. Despite its importance, research on strategy implementation has been limited and fragmented (Hrebiniak, 2006). Through a case study on two Indonesian telecommunication companies, as well as literature review, the author suggests the proposition that ‘hard factors’ such as organizational structure and control system, as well as ‘soft factors’ such as empowerment and corporate culture, play important roles in determining the success of strategy execution. To test the propositions, the paper also suggests a conceptual model that can be used in future research, in order to better understand the influence of the four antecedents on the success of strategy implementation.